Metodologi Pemahaman Hadis “Etos Kerja” dalam Kitab Kaifa Nata’ammal Ma’a as-Sunnah an-Nabawiyyah Karya Yusuf Al-Qaradhawi - Prasetyo, Bayu; Ridlo, Muhammad Abdurrasyid (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article aims to determine the understanding of the hadith about work ethic in the book Kaifa Nata'ammal Ma'a as-Sunnah an-Nabawiyyah from the perspective of Yusuf al-Qaradhawi. Hadiths about work ethic are often misunderstood by some communities as legality to avoid shari'a in worldly affairs, even though the prophet SAW did not intend this. This research is a qualitative study through a literature study approach with a content analysis study method sourced from primary and secondary data based on data collection which includes the book Kaifa Nata'ammal Ma'a as-Sunnah an-Nabawiyyah as primary data and the book as-Sunnah Mashdar li Ma'rifah wa al-Hadharah, Shahih Muslim, al-Minhaj fi Syarh Shahih Muslim as secondary data, as well as scientific articles and other supporting literature sources relevant to this research. This article seeks to answer the questions of how Yusuf al-Qaradhawi's contribution in the context of modern Islamic thought, how the hadith understanding methodology developed by Yusuf al-Qaradhawi, and how Yusuf al-Qaradhawi's understanding of the hadith about work ethic can contribute to building an inclusive and relevant Islamic view of the world of work in the contemporary era. the results of this study indicate that the hadith about ‘Work ethic’ in general is the prophet's instructions on how the order and behaviour of Muslims in the completion of a job, and in a specific sense speaks of professionalism in the world of work, namely respect for professional expertise or other fields of expertise that are universal.